Assessment of histopathology of wounds based on protein distribution detected by wound blotting. (November 2018) - Kitamura, Aya; Minematsu, Takeo; Nakagami, Gojiro; Sanada, Hiromi
Background: Shortening the duration of healing based on an accurate assessment is important in pressure ulcer management. This study focused on the peroxidase and alkaline phosphatase activity detected by wound blotting, a non-invasive method of collecting wound exudate, to establish a non-invasive and point-of-care assessment method for analyzing the histopathology of wounds using an animal model. Methods: Wounds were created on the dorsal skin of rats. Peroxidase and alkaline phosphatase activities in the wound exudate were detected by wound blotting on post-wounding days 1, 4, 7, and 10. Wound tissue was collected on the same sampling days. Peroxidase and alkaline phosphatase activity within the tissue and myeloperoxidase were visualized. Two types of peroxidase activities were detected by wound blotting: ring and non-ring signals. The histopathological features were compared between wounds with ring and non-ring signals. Results: The wounds with ring signals showed a high level of peroxidase activity, and histological analysis demonstrated that the secreted or deviated peroxidase activity originated from myeloperoxidase, indicating a strong inflammation reaction within the tissue. The histopathology of wounds related to the alkaline phosphatase signals was not identified. Conclusion: The results suggested that ring signals indicated a strong inflammatory reaction and that they could be used to assess non-visible inflammation.